Spatial distribution characteristics analysis and optimization of county-level settlements based on GIS - SUN Hua-sheng; HUANG Jing-feng; JIN Yan; DENG Rui; WANG Jie (浙江大学学报. 农业与生命科学版, 2007)
Land use, topography, administration, communication and geological disasters maps with a scale of 1∶50000, combined with population and economy data, were used in the quantitative analysis of spatial distribution characteristics of villages and towns in Xianju County by GIS. The results were used to help to plan the expanding directions of towns, decide villages that need to be migrated in the regions of geological disaster, high mountain and traffic inconvenience, and then some qualified villages were chosen as central villages by their attributes, so as to achieve the distribution optimization and offer references to settlement planning.